The Analysis of Buying and Selling Promo Products in Islamic Law Perspective - Wahyudi, M. Iman; Miftah, Ahmad Harisul; Saidu, Sabo Jamilu; Mustagfiroh, Mustagfiroh (Al Ahkam, 2024)
Buying and selling is a fundamental daily activity with a long history for humans. It is a social interaction that highlights the necessity for mutual assistance. Islamic law regulates this process to address concerns such as doubts about quality due to prices below market value. This study examines the Islamic perspective on such practices. The research adopts a qualitative approach, focusing on literature review and sourcing information from various sources such as Books, E-books, E-journals, Thesis, Al-Qur'an, and Hadiths. The study findings highlight the application of sharia principles in marketing and product promotion strategies within the context of Islamic law. The Islamic law governing the purchase and sale of promotional products entails the application of sharia principles in these transactions.